Conservative treatment of hallux rigidus: narrative review of scientific evidence - Herrera-Perez, Mario; González-Martín, David; Ruiz-Escobar, Javier; Viladot-Pericé, Ramón (Journal of the Foot & Ankle, 2021)
This study proposes an update on conservative treatment of hallux rigidus based on scientific evidence. This is a narrative review of 19 articles that analyzed conservative treatment of hallux rigidus in its different modalities. Conservative treatment is effective in approximately half of the patients with hallux rigidus, and footwear modifications, use of insoles, and hyaluronic acid injections are the most effective treatments, according to evidence-based medicine. Level of Evidence III; Therapeutic Studies; Systematic Review of Level III Studies.